Fatty Acid Synthase Contributes to Restimulation-Induced Cell Death of Human CD4 T Cells - Voss, Kelsey; Luthers, Christopher R.; Pohida, Katherine; Snow, Andrew L. (Frontiers in Molecular Biosciences, 2019)
Restimulation-induced cell death (RICD) is an apoptotic pathway triggered in activated effector T cells after T cell receptor (TCR) re-engagement. RICD operates at the peak of the immune response to ensure T cell expansion remains in check to maintain immune homeostasis. Understanding the biochemical regulation of RICD sensitivity may provide strategies for tuning the magnitude of an effector T cell response. Metabolic reprogramming in activated T cells is not only critical for T cell differentiation and effector functions, but also influences apoptosis sensitivity. We previously demonstrated that aerobic glycolysis correlates with optimum RICD sensitivity in human effector CD8 T cells. However, metabolic programming in CD4 T cells has not been investigated in this context. We employed a pharmacological approach to explore the effects of fatty acid and glycolytic metabolism on RICD sensitivity in primary human CD4 T cells. Blockade of fatty acid synthase (FASN) with the compound C75 significantly protected CD4 effector T cells from RICD, suggesting that fatty acid biosynthesis contributes to RICD sensitivity. Interestingly, sphingolipid synthesis and fatty acid oxidation (FAO) were dispensable for RICD. Disruption of glycolysis did not protect CD4 T cells from RICD unless glyceraldehyde-3-phosphate dehydrogenase (GAPDH) enzymatic activity was targeted specifically, highlighting important differences in the metabolic control of RICD in effector CD4 vs. CD8 T cell populations. Moreover, C75 treatment protected effector CD4 T cells derived from naïve, effector memory, and central memory T cell subsets. Decreased RICD in C75-treated CD4 T cells correlated with markedly reduced FAS ligand (FASL) induction and a Th2-skewed phenotype, consistent with RICD-resistant CD4 T cells. These findings highlight fatty acid synthase as a critical metabolic potentiator of RICD in human effector CD4 T cells.